An FPGA based Real time Implementation of Nosé hoover Chaotic System using different numerical Techniques - Garg, Ayush; Yadav, Bhola; Sahu, Kaustuv; Suneja, Kriti (International Conference on Advanced Computing and Communication Systems (Online), 2021)
In this paper, we have implemented the Nosé-Hoover chaotic generator by numerically coding the differential equations in Python and modeling them in Xilinx Kintex 7 FPGA development environment using Euler's, Heun's, and Runge Kutta's 4th order-based algorithms in Verilog HDL. The performance of these algorithms has been analyzed by comparing Slice LUTs used, delay, DSPs, etc. The accuracy of the HDL implementation of each algorithm has been analyzed by calculating Root Mean Square Error(RMSE). In addition, the computation time of PC-based and FPGA-based implementation also have been compared for each algorithm.